Evidence for involvement of Th17 type responses in post kala azar dermal leishmaniasis (PKDL). - Gajendra Kumar Katara; Nasim Akhtar Ansari; Avninder Singh; V Ramesh; Poonam Salotra (Public Library of Science (PLoS), 2012)
BACKGROUND: Post kala-azar dermal leishmaniasis (PKDL), a dermal sequel of visceral leishmaniasis, caused by Leishmania donovani, constitutes an important reservoir for the parasite. Parallel functioning of counter acting immune responses (Th1/Th2) reflects a complex immunological scenario, suggesting the involvement of additional regulatory molecules in the disease pathogenesis. METHODOLOGY/PRINCIPAL FINDINGS: In the present study, human cytokine/chemokine/receptor specific cDNA array technique was employed to identify modulations in gene expression of host immuno-determinants during PKDL, followed by evaluation of Th17 type responses by analyzing mRNA and protein expression of Th17 markers (IL-23, IL-17, RORγt) and performing functional assays using Leishmania antigen (TSLA) or recombinant (rec)IL-17. Array analysis identified key immuno-regulatory molecules including cytokines (TNF-α, IFN-γ, IL-10, IL-17), chemokines (MCP-1, MIP-1α), apoptotic molecules (FasL, TRAIL, IRF-1) and receptors (CD40, Fas). Up regulation in lesional expression of Th17 markers was observed during PKDL compared to control (IL-17 and IL-23, P = 0.0008; RORγt, P = 0.02). In follow-up samples, chemotherapy significantly down regulated expression of all markers. In addition, lesional expression of IL-17 was confirmed at protein level by Immuno-histochemistry. Further, systemic presence of Th17 responses (IL-17 and IL-23) was observed in plasma samples from PKDL patients. In functional assays, TSLA stimulated the secretion of IL-17 and IL-23 from PBMCs of PKDL patients, while recIL-17 enhanced the production of TNF-α as well as nitric oxide (NO) in PKDL compared to control (TNF-α, P = 0.0002; NO, P = 0.0013). Further, a positive correlation was evident between lesional mRNA expression of IL-17 and TNF-α during PKDL. CONCLUSION/SIGNIFICANCE: The results highlight key immune modulators in PKDL and provide evidence for the involvement of Th17 type responses in the disease pathogenesis.